PTU-107 Video outpatient services: can patient choice in how to attend be a success?. Issue 2 (June 2019) - Cannon, Philip; Fraser, Craig; Siu, Wilson; Thomson, John
Abstract : Introduction: Recent technological advancements have created the opportunity to radically transform how outpatient services are delivered. Citizens with chronic relapsing/remitting disease such as Inflammatory Bowel Disease (IBD) are often required to attend regular follow up clinic appointments with the associated travel and time off work creating considerable effects on carbon emissions and the wider economy. Methods: As part of a wider program of work to establish a patient focussed outpatient service a pilot study was instigated where all patients were offered the option of attending their IBD appointment using a video clinic platform (Attend Anywhere®). This abstract describes the evaluation phase of patient initiated video appointments from patient and clinician viewpoints. The uptake of video appointments was recorded from the Patient Administration System along with demographics of the tele-medicine (video) and anchi-medicine (traditional clinic) groups. Patient perspectives were captured by an online questionnaire presented to them on concluding the video appointment and clinician perspective was captured with the clinic documentation. Results: During the 7 month study period 194 (12%) opted for a video appointment of which 85 (41%) completed the patient questionnaire. There were no significant differences in demographics or proportion of did not attend (DNA) appointments between the groups. However, 77% of the video group were noted to have minimal symptoms. In the patient questionnaire, 85 (100%) indicated they would use video again, 80 (94%) found it more convenient than attending the hospital and 54 (64%) indicated they had not had to take time off work. The average travel saved was 117 miles per appointment. However, 33% experienced technical issues during the consultation. The clinician data indicated that 80% of the video consultations had been entirely successful with the majority of unsuccessful video consultations being completed by telephone. Two patients required a further anchi-medicine appointment for examination and three required to attend for blood tests only available at the clinic. Conclusions: In line with the increasing use of technology in our society, this study has indicated that the patient can successfully make the choice of how to attend the clinic with little, if any, impact on the wider clinic service. However, such changes must be planned and prepared for so that other clinic processes such as booking and blood investigations procedures can be accommodated in the new clinic model. As with all technology adoption there is a curve of uptake, as the technology underpinning video clinics becomes mainstream it is anticipated that video will become an increasingly popular method of outpatient review technology with patients and clinicians.